Tenement nation : working-class cosmopolitanism in Edinburgh - Tooley, Christa Ballard (Framing the global book series., 2023)
"In Tenement Nation, Christa Ballard Tooley explores the battle for a neighborhood called the Canongate in Edinburgh's Old Town. Tooley's insightful study of the working-class Canongate community as they negotiate gentrification plans offers a complex view of class and nation. The threat of the Canongate's redevelopment motivated many throughout Edinburgh to lend their support to the residents' campaign. Against such development projects, alliances formed between upper-class heritage supporters and working-class urban residents, all of whom turned to institutions such as the European Union and UNESCO for support in restricting commercial development"--